THE BONE TISSUE CHANGES INVESTIGATION WITH METABOLIC SYNDROME (Proceedings of International Educators Conference, 2024)
Objective: This study aims to estimate bone tissue changes in experimental animals with metabolic syndrome (MS) using Multislice Computed Tomography (MSCT). Metabolic syndrome, characterized by obesity, insulin resistance, hypertension, and dyslipidemia, has been linked to adverse effects on bone health. By employing MSCT, a non-invasive imaging modality, we seek to quantitatively assess alterations in bone mineral density (BMD) and bone volume (BV) in affected animals. Methods: Experimental metabolic syndrome was induced in a cohort of rodents through a high-fat diet regimen. A control group was maintained on a standard diet. Baseline MSCT scans were performed on all animals prior to diet intervention, followed by periodic scans at regular intervals. High-resolution 3D images of the femur, tibia, and spine were reconstructed for detailed analysis. Parameters such as BMD, BV, and trabecular microarchitecture were quantitatively evaluated using specialized software. The data were statistically analyzed to compare changes between the control and experimental groups over time. Results: Preliminary findings indicate significant reductions in BMD and BV in animals with metabolic syndrome compared to controls. Notable deterioration in trabecular microarchitecture was observed, suggesting compromised bone quality. The extent of bone tissue changes correlated with the severity of metabolic abnormalities, highlighting the detrimental impact of metabolic syndrome on skeletal health. Conclusion: MSCT proved to be a valuable tool for non-invasively monitoring bone tissue changes in metabolic syndrome. The study underscores the importance of early detection and intervention in metabolic disorders to mitigate potential bone-related complications. Future research should focus on exploring therapeutic strategies to preserve bone health in individuals with metabolic syndrome.